2018
DOI: 10.1111/gcb.14165
|View full text |Cite
|
Sign up to set email alerts
|

Limited evidence forCO2‐related growth enhancement in northern Rocky Mountain lodgepole pine populations across climate gradients

Abstract: Forests sequester large amounts of carbon annually and are integral in buffering against effects of global change. Increasing atmospheric CO may enhance photosynthesis and/or decrease stomatal conductance (g ) thereby enhancing intrinsic water-use efficiency (iWUE), having potential indirect and direct benefits to tree growth. While increasing iWUE has been observed in most trees globally, enhanced growth is not ubiquitous, possibly due to concurrent climatic constraints on growth. To investigate our incomplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 92 publications
(196 reference statements)
3
22
0
1
Order By: Relevance
“…Our conclusion that a CO 2 fertilization effect was not occurring in these stands is inconsistent with a common expectation that such an effect should be widespread and prominent (Arora et al, ; Luyssaert et al, ; Matthews, ; Norby et al, ; Zhu et al, ) as well as with some local and large‐scale inventory studies (McMahon et al, ; Pan et al, ). However, our results concur with the observed lack of a CO 2 ‐induced growth response in mature natural stands illustrated via manipulative experiment (Körner et al, ), inventories (Chen, Luo, Reich, Searle, & Biswas, ) and tree rings (Camarero et al, ; Gedalof & Berg, ; Groenendijk et al, ; Reed, Ballantyne, Cooper Leila, & Sala, ; van der Sleen et al, ). Other recent large‐scale analyses reveal a high degree of heterogeneity in growth responses to elevated CO 2 (Charney, D., Babst, F., Poulter, B., Record, S., Trouet, V., M., Frank, D., Evans, M., E., Evans, M., E., Evans, M., E., Evans, M., & E. K., 2016; Girardin et al, ; Kelsey, Redmond, Barger, & Neff, ; Tei et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our conclusion that a CO 2 fertilization effect was not occurring in these stands is inconsistent with a common expectation that such an effect should be widespread and prominent (Arora et al, ; Luyssaert et al, ; Matthews, ; Norby et al, ; Zhu et al, ) as well as with some local and large‐scale inventory studies (McMahon et al, ; Pan et al, ). However, our results concur with the observed lack of a CO 2 ‐induced growth response in mature natural stands illustrated via manipulative experiment (Körner et al, ), inventories (Chen, Luo, Reich, Searle, & Biswas, ) and tree rings (Camarero et al, ; Gedalof & Berg, ; Groenendijk et al, ; Reed, Ballantyne, Cooper Leila, & Sala, ; van der Sleen et al, ). Other recent large‐scale analyses reveal a high degree of heterogeneity in growth responses to elevated CO 2 (Charney, D., Babst, F., Poulter, B., Record, S., Trouet, V., M., Frank, D., Evans, M., E., Evans, M., E., Evans, M., E., Evans, M., & E. K., 2016; Girardin et al, ; Kelsey, Redmond, Barger, & Neff, ; Tei et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…The mixed model residuals at our sites were positively related to temperature (Supporting Information Table S3), which might indicate that tree productivity in these old‐growth forests is temperature limited. Soil moisture deficits can constrain growth in cold regions, despite rising temperatures and CO 2 concentrations (Girardin et al, ; McDowell et al, ; Tei et al, ; Williams, ), and there is evidence of growth declines related to water stress in subalpine forests (Carrer & Urbinati, ; Reed et al, ). Moisture deficits are possible at our sites, but they are unlikely, because mean summer precipitation (MSP) had increased in the 20th century at all sites except Mt.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous literature, we found an enhancement in iWUE over the years regardless of topography (Peñuelas et al, 2011; Reed et al, 2018; Wu et al, 2015). Rates of iWUE increase were within average responses seen for the same species (0.26–0.37 μmol mol −1 per year) (Gómez‐Guerrero et al, 2013), but one site (3500‐NW) contrasts and exhibited an increasing rate close to that found in tropical trees in response to CO 2 stimulation of photosynthesis (≈0.7 μmol mol −1 per year) (Figure 6) (Loader et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Rising temperature and atmospheric CO 2 have been not consistently associated with increased tree growth or iWUE across biomes (Gómez‐Guerrero et al, 2013; Granda et al, 2017; Linares & Camarero, 2012; Peñuelas et al, 2011; Reed et al, 2018; Wu et al, 2015). As in many of those previous studies, we found that only a small subset of sampled trees exhibited a significant increase in productivity increase over the past 17 years (e.g., trees at the 3500‐NW site), suggesting that P. hartwegii 's trees have not benefited from recent warming conditions or from rising atmospheric CO 2 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many subsequent studies, records with interannual resolution sampled over too short of a period or were aimed at addressing the impact of thinning treatments that reduced stand occupancy (Leavitt, Wright, & Long, 2002;Marshall & Monserud, 1996;McDowell et al, 2006;McDowell, Allen, & Marshall, 2010;Roden & Ehleringer, 2007;Sohn et al, 2014). Alternatively, other tree-ring carbon isotope studies of Western US forests used pentadal or decadal sampling units that preclude determinations of sensitivity to meteorological drought on a year-by-year basis (Feng, 1998;Knapp & Soulé, 2011;Knapp, Soulé, & Maxwell, 2013;Leavitt & Long, 1988;Reed, Ballantyne, Cooper, & Sala, 2018;Soulé & Knapp, 2015). Additional ponderosa pine treering carbon isotope records with interannual resolution have been developed but offer no insight on responses to competition since the sites chosen had widely spaced trees to help ensure the stability of climate responses (Szejner et al, 2016;Szejner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%